The BDNF Val66Met polymorphism and anxiety: support for animal knock-in studies from a genetic association study in humans - Montag, Christian; Basten, Ulrike; Stelzel, Christine; Fiebach, Christian; Reuter, Martin (Psychiatry research, 2010)
Mounting evidence shows that the brain derived neurotrophic factor (BDNF) plays a crucial role in depression and anxiety. The discovery of a functional variant of the BDNF gene - the BDNF Val66Met polymorphism - led to new insights into the molecular genetic mechanisms underlying these emotional disorders. Although there is evidence from animal research that the homozygous BDNF 66Met variant is associated with anxiety-like behaviour, findings from personality research using self-report-measures as indicators of trait anxiety are heterogenous. Recent seminal findings from a study using a knock-in mouse design suggest that this Met66Met group is of particular interest for the investigation of the molecular genetic mechanisms of anxiety and anxiety-related personality traits in humans. In a sample of 610 Caucasian participants, subjects homozygous for the 66Met allele scored significantly higher than Val66 allele carriers on anxiety-related facets of the construct 'harm avoidance' (i.e., 'anticipatory worry' and 'fear of uncertainty') of the Temperament and Character Inventory. This finding adds to a small plurality of studies that associates the 66Met allele, rather than the Val66 allele, with higher anxiety scores. Importantly, the present results furthermore suggest that it is the occurrence of not one but two 66Met alleles that is associated with high trait anxiety.
Gesehen am 03.05.2023